Prevalence of Waja‘al-Mafāṣil in the patients of Dhayābīṭus, attending NIUM hospital: a cross-sectional study - Aamir, B. Mohammed; Haseeb Ansari, Abdul (International Journal Of Community Medicine And Public Health, 2024)
Background: Osteoarthritis (OA) is the most common form of arthritis typically affecting the various joints with a prevalence of 22-39% in India. Diabetes is a major health issue that has reached alarming levels. Diabetes and osteoarthritis share common risk factors and due to this factor, this study was carried out to know the prevalence of osteoarthritis among diabetic patients, visiting the hospital of NIUM, Bengaluru. Methods: It is a hospital-based cross-sectional study, which was carried out with a sample size of 250 patients of both genders, selected through purposive sampling. The duration of the study was one year (March 2022 to February 2023). A predesigned and semi-structured schedule included information related to demography, socioeconomic status, anthropometry, personal habits, etc. were obtained. Results: Among enrolled (250) diabetic patients, the overall prevalence of osteoarthritis was 54.4% (136) which was statistically significant (p>0.001). Among 136 diabetic patients with osteoarthritis, the highest prevalence (46.32%) in the age group 50-60 years, the lowest prevalence (8.1%) was seen in the age group 30-40 years. The Balghamī type was observed in 85% of patients while in 15% it was observed as Murakkab type. Conclusions: The present study showed that the prevalence of OA was found to be 54.4% among diabetic patients, in which Balghamī type Waja‘al-Mafāṣil was of maximum (85%), which may be interpreted that the main cause of Waja‘al-Mafāṣil was the Balghamī Mizāj of the patients, that is mentioned in classical Unani literatures, it means that the observations of Unani physicians were very keen and perfect.